National Brazilian survey on the outcomes of hepatitis c retreatment in patients non-responders to direct antiviral agents - Ferraz, Maria Lúcia Gomes; Piccoli, Leonora de Zorzi; Rezende, Rosamar; Borba, Luiz Augusto; Junior, Alcindo Pissaia; Cheinquer, Hugo; Silva, Giovanni Faria [UNESP]; Ferreira, Paulo Roberto Abrão; Villela-Nogueira, Cristiane Alves; Mazo, Daniel Ferraz; Souza, Fernanda Fernandes; Codes, Liana; et al. (Elsevier, 2022)
Background and aims: Treatment of hepatitis C with direct antiviral agents (DAA) is associated with almost 95% of sustained virological response. However, some patients need retreatment. In Brazil, it should be done according to the Ministry of Health guidelines, frequently updated to include newly available drugs. This study aimed to conduct a national survey about the characteristics and outcomes of retreatment of hepatitis C in previously non-responders to DAAs. Patients and methods: Institutions from all over the country were invited to participate in a national registry for retreatment, including information about clinical and epidemiological characteristics of the patients, type and outcomes of retreatment regimens. Only patients previously treated with interferon-free regimens were included. Results: As previous treatments the distribution was: SOF/DCV (56%), SOF/SIM (22%), 3D (11%), SOF/LED (6%) and SOF/RBV (5%). For retreatment the most frequently used drugs were SOF/GP (46%), SOF/DCV (23%) and SOF/VEL (11%). From 159 patients retreated, 132/159 (83%) had complete information in the registry and among them only seven patients were non-responders (SVR of 94.6%). All retreatments were well tolerated, without any serious adverse events or interruptions. Conclusion: The retreatment of patients previously non-responders to DAAs was associated with high rate of SVR in this sample of Brazilian patients. This finding allows us to conclude that the retreatment options available in the public health system in Brazil are effective and safe and are an important component of the strategy of elimination of hepatitis C in our country.
Keywords: DAA; Hepatitis C; Retreatment; Sustained virological response